Caribbean trade & investment report 2000 : dynamic interface of regionalism & globalisation (Caribbean Community Secretariat. Economic Intelligence & Policy Unit GeorgetownGY, 2000)
Focuses on trade and investment and the implications for the process of economic transformation.
Keywords: TRADE